2016
DOI: 10.1063/1.4940887
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic electrochemical biosensor based on multiwall carbon nanotube/ferrocene for genomic DNA detection of Mycobacterium tuberculosis in clinical isolates

Abstract: Herein we present a microfluidic-multiplexed platform that integrates electrochemical sensors based on carbon nanotubes associated with ferrocene as redox marker (carbon nanotube (CNT)/ferrocene) for direct detection of pathogenic viral DNA from Hepatitis C and genomic DNA from Mycobacterium tuberculosis in clinical isolates. By operating the fluidic device under high flow (150 μl/min), the formation of a very thin depletion layer at the sensor surface (δS = 230 nm) enhances the capture rate up to one DNA stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…This system resulted in rapid detection of melatonin, tryptophan and serotonin in periods shorted than 150 s (Gomez et al 2015). Furthermore, it was found that an amperometric sensor could be made of CNTs and ferrocene (as a redox-responsive reporter) that was applied in order to detect pathogenic viral DNA from hepatitis C and genomic DNA from Myocobacterium tuberculosis with high sensitivity (Zribi et al 2016). …”
Section: Lab-on-a-chipmentioning
confidence: 99%
“…This system resulted in rapid detection of melatonin, tryptophan and serotonin in periods shorted than 150 s (Gomez et al 2015). Furthermore, it was found that an amperometric sensor could be made of CNTs and ferrocene (as a redox-responsive reporter) that was applied in order to detect pathogenic viral DNA from hepatitis C and genomic DNA from Myocobacterium tuberculosis with high sensitivity (Zribi et al 2016). …”
Section: Lab-on-a-chipmentioning
confidence: 99%
“…Biosensors for detecting the proper antigen or the immunological markers associated with the infections have demonstrated to be an efficient tool for simple and rapid diagnosis in real time and complex samples. Table 2 [72,[99][100][101][102][103][104][105][106][107][108][109][110][111][112] shows some examples of methods using electrochemical DNA sensors or immunosensors characterized by their low limits of detection.…”
Section: Electrochemical Affinity Biosensors For Detection Of Tubercumentioning
confidence: 99%
“…Direct detection of a genomic DNA sample, without pre-analytical and amplification steps, allowed shortening analysis times and minimizing system complexity and other errors issued from contamination occurring in these further steps. Since accurate diagnostics need specific detection of very small amounts of DNA, there is a need to develop simple label-free DNA hybridization platforms able to perform highly sensitive and specific direct analyses [16]. Moreover, DNA sensors are widely used in diagnostic tests for early cancer and mutation detection, analysis of gene sequences, forensic investigation and assessment of medical treatment [17,18].…”
Section: Electrochemical Dna Sensors Involving Carbon Nanomaterialmentioning
confidence: 99%
“…They are critically discussed in the following sections with the aim of showing the enormous potential of DNA electrochemical devices in the field of medical and clinical diagnostics. Furthermore, electrochemical detection is fully compatible with cost-effective hand held microfluidic platforms that bring the possibility of manipulating tiny amounts of samples (<µL) for fast analysis [16]. …”
Section: Electrochemical Dna Sensors Involving Carbon Nanomaterialmentioning
confidence: 99%
See 1 more Smart Citation